2017
DOI: 10.1016/j.jvb.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Looking forward: Career identity formation and the temporal orientations of young Australians

Abstract: Her research interests include the life trajectories of young people living in Australia, and the attitudes of young Australians towards ethnic and cultural diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
(54 reference statements)
2
15
0
Order By: Relevance
“…Students with high FTP were significantly more likely to be working during the survey period. This supports previous studies which have demonstrated that future orientation predicts a variety of lifetime social, economic, and career-oriented behaviors ( Laghi et al, 2013;Golsteyn et al, 2014;Taber & Blankemeyer, 2015;Laughland-Booÿ et al, 2017). It also suggests that college students view employment while in school as more than just a means for meeting current financial obligation, but as a way to prepare for their occupation after graduation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Students with high FTP were significantly more likely to be working during the survey period. This supports previous studies which have demonstrated that future orientation predicts a variety of lifetime social, economic, and career-oriented behaviors ( Laghi et al, 2013;Golsteyn et al, 2014;Taber & Blankemeyer, 2015;Laughland-Booÿ et al, 2017). It also suggests that college students view employment while in school as more than just a means for meeting current financial obligation, but as a way to prepare for their occupation after graduation.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, men are typically focused on goals related to employment and financial security, whereas women are concerned more with goals for marriage and family. The stereotypical views of women as housewives may impact the future career goals of female students causing them to contemplate their future family responsibilities rather than giving attention to professional career exploration (Laughland-Booÿ et al, 2017). The degree to which these gender-based perceptions of future responsibilities impact the employment decisions of college students should be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…An effect of self-esteem on career identity has also been identified in previous studies [17,19,28]. According to a qualitative study of young Australians, subjective achievement affected the formation of career identity [55]. Therefore, a career development program with activities and experiences promoting positive self-evaluation may be effective.…”
Section: Discussionmentioning
confidence: 68%
“…Laughland-Booÿ et al ( 2017) identified four temporal outlooks classified as adaptable, controllable, predictable and uncertain. Adaptable outlooks describe a general openness to situations and circumstances; controllable outlooks are characterised by a sense of control and self-determination; predictable outlooks rely on a perceived certainty and continuity to one's environment; and uncertain outlooks interpret life through a lens of ambiguity or uncertainty (Laughland-Booÿ et al, 2017). We suggest that these four temporal outlooks exist within each time perspective and provide greater and more observable nuance between people's temporal orientations.…”
Section: Temporality Of Happinessmentioning
confidence: 87%
“…We based our methodological framework on theory pertaining to abductive research strategy, which explores everyday lay concepts produced by participants to explain social phenomena (Blaikie, 2007;Laughland-Booÿ et al, 2017). We adopt the ontological assumption that the world exists independently of perceptions and theories, yet our understanding of this reality is socially constructed (Hoddy, 2019).…”
Section: Methodsmentioning
confidence: 99%